"A definite feel‐it moment": Embodiment, externalisation and emotion during chair‐work in compassion‐focused therapy. Issue 1 (8th July 2019) - Bell, Tobyn; Montague, Jane; Elander, James; Gilbert, Paul
Abstract: Chair‐work is an experiential method used within compassion‐focused therapy (CFT) to apply compassion to various aspects of the self. This is the first study of CFT chair‐work and is focused on clients' lived experiences of a chair‐work intervention for self‐criticism. Twelve participants with depression were interviewed following the chair‐work intervention and the resulting data were examined using interpretative phenomenological analysis. Three superordinate themes were identified: "embodiment and enactment, " "externalising the self in physical form" and "emotional intensity." The findings suggest the importance of accessing and expressing various emotions connected with self‐criticism, whilst highlighting the potential for client distress and avoidance during the intervention. The role of embodying, enacting and physically situating aspects of the self in different chairs is also suggested to be an important mechanism of change in CFT chair‐work. The findings are discussed in terms of clinical implications, emphasising how core CFT concepts and practices are facilitated by the chair‐work process.